2004
DOI: 10.1590/s0102-311x2004000800016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Integrated Management of Childhood Illness (IMCI) on health worker performance in Northeast-Brazil

Abstract: A multi-country evaluation is being carried out in Brazil and four other countries to determine the effectiveness, cost, and impact of the Integrated Management of Childhood Illness (IMCI). We examine the effect of IMCI on the quality of health care provided to children under five visiting health facilities. A health facility survey was conducted at 24 facilities (12 with IMCI) in each of four States in the Northeast. We assessed the quality of care provided to children between 2 months and 5 years attending t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 6 publications
2
50
1
9
Order By: Relevance
“…20 In other studies, nurses and female providers have also been found to deliver better care than doctors and male providers, respectively. 21,22 In our study, female health-care providers gave better care to younger children and showed better performance than their male counterparts in 2006, but doctors performed better than other providers.…”
Section: Discussionmentioning
confidence: 50%
“…20 In other studies, nurses and female providers have also been found to deliver better care than doctors and male providers, respectively. 21,22 In our study, female health-care providers gave better care to younger children and showed better performance than their male counterparts in 2006, but doctors performed better than other providers.…”
Section: Discussionmentioning
confidence: 50%
“…Por outro lado, Samico et al 18 , ao avaliar a implantação da atenção à saúde da criança em dois municípios do Estado de Pernambuco, em unidades de saúde do PSF treinadas na estratégia AIDPI, não treinadas e em unidades convencionais, observaram que a ação de crescimento e desenvolvimento apresentou deficiente aplicação nos três tipos de casos, sendo os resultados piores entre os profissionais não treinados e nas unidades convencionais. Em um outro estudo realizado por Amaral et al 19 Por isso, as consultas são um momento importante para a coleta de medidas antropométricas e registro no gráfico como uma forma mais adequada para acompanhar o crescimento de uma criança nos serviços de saúde.…”
Section: Discussionunclassified
“…The downside is that family health workers have neither a career structure nor job security or fringe benefi ts that other civil servants are entitled to. As a result, job satisfaction is typically below par and staff turnover is high, 48,49 leading to discontinuities in patients' care.…”
Section: Human Resources Challengesmentioning
confidence: 99%